Edification-Based Leadership Development: Integrating Behavioral and Managerial Design Change Future-Ready Elementary Schools Principals in Urban and Rural Settings - Suryana, Asep; Sururi, Sururi; Suryadi, Suryadi; Suharto, Nugraha; Dikdik, Asep; Barlian, Iqbal Nugraha; Nurjannah, Siti (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study investigates how elementary school principals in urban and rural settings develop future-ready leadership through integrating behavioral and managerial design change dimensions within an edification-based framework to address digital transformation challenges in Indonesian elementary education. Methodology: A mixed exploratory qualitative design with component analysis was employed, using structured observations and interviews with contrasting questions. Ten elementary school principals from Bandung City and West Bandung Regency were selected via purposive sampling. Data were analyzed using ATLAS.ti software through systematic thematic coding of non-numerical textual data. Main Findings: Urban schools in Bandung City demonstrated higher digital adaptability, innovative supervision, and active professional development supported by adequate infrastructure and collaborative culture. Rural schools in West Bandung Regency exhibited conventional leadership patterns constrained by limited technology access. Two integrated leadership stages emerged: Behavior Design Change (digital leadership, open-mindedness, efficacy, foresight) and Managerial Design Change (network, digital organization, transition management, digital transformation, innovation strategy). Novelty/Originality of this study: This study introduces an edification-based leadership development framework integrating behavioral and managerial design change dimensions specifically for elementary school principals. It advances existing knowledge by providing empirical evidence of urban–rural digital leadership disparities in Indonesia and offering a contextualized, culturally-responsive model for developing future-ready school leaders.